Pembelajaran Kooperatif Tipe Jigsaw Menggunakan LKS Terstruktur Dapat Meningkatkan Kemampuan Pemahaman Konsep Struktur dan Fungsi Tumbuhan Kelas VIII SMP Negeri 1 Brang Rea Kabupaten Sumbawa Barat - Aswar Anas (Jurnal LENTERA: Jurnal Studi Pendidikan, 2020)
The background of this research is the incomplete learning of students before the material structure and function of plants in class VIII students of SMP Negeri 1 Brang Rea. The research objective is to determine the use of structured worksheets to improve the ability to understand the concept of structure and function of plants in class VIII SMP Negeri 1 Brang Rea on the structure and function of plants for the 2019/2020 academic year. This research was conducted at SMP Negeri 1 Brang Rea, West Sumbawa Regency in class VIII students for the 2019/2020 school year which consisted of 32 students. This research is a Classroom Action Research which consists of two basic competencies that are divided into two cycles. From each cycle, data were obtained in the form of observations and evaluation results which were analyzed quantitatively. These data are collected and managed with the indicators used, if ± 80% of all students have obtained a value of ± 70 then the hypothesis is accepted. From the results of data processing, the percentage of completeness of learning in the first cycle was 76.47% and the second cycle was 94.12%. These results indicate an increase in each cycle. So it can be concluded that by using structured worksheets in jigsaw-type cooperative learning, plant structure and function materials can improve the ability to understand the concept of plant structure and function in class VIII SMP Negeri 1 Brang Rea, West Sumbawa Regency, 2019/2020 academic year